Quinoxaline‐Based D–A Copolymers for the Applications as Polymer Donor and Hole Transport Material in Polymer/Perovskite Solar Cells. Issue 22 (10th October 2021) - Sun, Chenkai; Zhu, Can; Meng, Lei; Li, Yongfang
Abstract: Polymer solar cells (PSCs) have achieved great progress recently, benefiting from the rapid development of narrow bandgap small molecule acceptors and wide bandgap conjugated polymer donors. Among the polymer donors, the D–A copolymers with quinoxaline (Qx) as A‐unit have received increasing attention since the report of the low‐cost and high‐performance D–A copolymer donor based on thiophene D‐unit and difluoro‐quinoxalline A‐unit in 2018. In addition, the weak electron‐deficient characteristic and the multiple substitution positions of the Qx unit make it an ideal A‐unit in constructing the wide bandgap polymer donors with different functional substitutions. In this review article, recent developments of the Qx‐based D–A copolymer donors, including synthetic method of the Qx unit, backbone modulation, side chain optimization, and functional substitution of the Qx‐based D–A copolymers, are summarized and discussed. Furthermore, the application of the Qx‐based D–A copolymers as hole transport material in perovskite solar cells (pero‐SCs) is also introduced. The focus mainly on the molecular design strategies and structure–properties relationship of the Qx‐based D–A copolymers, aiming to provide a guideline for developing high‐performance Qx‐based D–A copolymers for the applications as donor in PSCs and as hole transport material in pero‐SCs. Abstract : Recent developments of the quinoxaline‐based D–A copolymers for the applications as polymer donor in polymer solar cells and as hole transport material in perovskite solar cells are reviewed.